1966
DOI: 10.1113/jphysiol.1966.sp007893
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological study of chelonian skeletal muscle

Abstract: SUMMARY1. Membrane properties of fibres of the retractor capitis muscles of the tortoise, Testudo graeca, and of the terrapin, Pseudemys elegans scripta, have been investigated with electrophysiological techniques. The features studied were qualitatively and quantitatively similar in both.2. Fibres are electrically excitable and many extend through 90 % of the length of the muscle. In the tortoise muscle conduction velocity was 0-8 m/sec in hibernating animals, and 1-3 m/sec in active animals.3. Resting potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is possible that such intermediate fibres do occur in snake, but were missed in this study. Levine (1966) found in chelonian retractor capitis muscles that many fibres were multiterminally (though focally) innervated. These fibres had normal APs with overshoot, and Rm and Cm were respectively about 4860 Q cm2 and 79 ,uF/cm2, values more characteristic of twitch than tonic fibres.…”
Section: Membrane Cons8tant8 Of Tonic Fibrementioning
confidence: 91%
See 1 more Smart Citation
“…It is possible that such intermediate fibres do occur in snake, but were missed in this study. Levine (1966) found in chelonian retractor capitis muscles that many fibres were multiterminally (though focally) innervated. These fibres had normal APs with overshoot, and Rm and Cm were respectively about 4860 Q cm2 and 79 ,uF/cm2, values more characteristic of twitch than tonic fibres.…”
Section: Membrane Cons8tant8 Of Tonic Fibrementioning
confidence: 91%
“…Levine (1966) Fatt & Katz (1951; using square pulse analysis and intracellular recording). Mean values in frog were A = 2-4 mm (diameter = 137 is), Rm = 4100 Q cm2.…”
Section: Membrane Cons8tant8 Of Tonic Fibrementioning
confidence: 99%
“…The electrophysiological methods used were unsuitable for determining the number of inputs to a poly-axonally innervated excitable fibre. Even some of the fibres in which only one action potential was recorded may have received more than one input, but if the lowest threshold axon supplied the fibre at a point nearer the electrode than did the others, only a single potential would be seen because of spike collision (see also Levine, 1966). Estimates of passive properties might be useful in distinguishing these fibres from those with a single en plaque terminal and it is unfortunate that this was not possible in these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…His findings suggested their presence in reptiles. Levine (1966) found that muscle fibres of the tortoise which exhibit a maintained contractile response to acetylcholine application are able to produce propagated action potentials. Similar findings by Ginsborg (1960) on avian muscle also suggested that responses to acetylcholine application, alone, were insufficient indicators of a muscle's functional properties.…”
Section: Introductionmentioning
confidence: 99%